Determinants of Organizational Commitment - Fajar Al Hadi, Andi; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This research aims to examine the influence of the work environment and organizational culture on organizational commitment, mediated by work stress at the Bank Indonesia Representative Office, North Sumatra Province. Bank Indonesia is an independent state institution tasked with considering economic policy in Indonesia. Apart from these functions, Bank Indonesia has a scope of internal work which is under the management of the Internal Management sector. One of the sections under Bank Indonesia's internal division is the Human Resources (HR) section. Bank Indonesia HR has several tasks in managing employees, one of which is processing employee health data. The results of this research are as follows: Organizational Culture has a positive and insignificant effect on Organizational Commitment with an original sample value of 0.129 and an ap value of 0.205. Organizational Culture has a negative and significant effect on Job Stress with a sample value of -0.498 and ap value of 0.000. Work Environment has a positive and insignificant effect on Organizational Commitment with an original sample value of 0.483 and ap value of 0.002. Work Environment has a negative and significant effect on Work Stress with an original sample value of -0.476 and ap value of 0.000. Job Stress has a negative and significant effect on Organizational Commitment with an original sample value of -0.107 and ap value of 0.308. Organizational Culture has a positive and significant effect on Organizational Commitment through Work Stress indirectly with an original sample value of 0.053 and ap value of 0.315. Work Environment has a positive and insignificant effect on Organizational Commitment through Job Stress with an original sample value of 0.051 and ap value of 0.306.